2022
DOI: 10.3390/ma15186326
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Commercially Available Premix UHPC-Based 3D Printable Concrete

Abstract: Several recent studies have attempted to formulate printable cementitious materials to meet the printing requirements, but these materials are designed to work with specific printing equipment and printing configurations. This paper aims to systematically develop and perform characterization of a commercially available ultra-high-performance concrete-class material (UHPC) modified to be printable. Four percentages of superplasticizer were used (100%, 94%, 88%, 82%) to adjust the UHPC mixture for 3D-printing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…Different authors showed that 3 percent by volume of carbon fibers with a length of 3 millimeters can significantly increase the flexural strength of concrete up to 120 MPa [21]. Similarly, a study shows that 3D-printable Ultra-High-Performance Concrete (UHPC) had a lower compressive strength (32-56 %) than mold-cast UHPC [22].…”
Section: Introductionmentioning
confidence: 99%
“…Different authors showed that 3 percent by volume of carbon fibers with a length of 3 millimeters can significantly increase the flexural strength of concrete up to 120 MPa [21]. Similarly, a study shows that 3D-printable Ultra-High-Performance Concrete (UHPC) had a lower compressive strength (32-56 %) than mold-cast UHPC [22].…”
Section: Introductionmentioning
confidence: 99%